Tomada de contas especial : análise da efetividade do instrumento aplicada ao caso de Minas Gerais - Quintão, Cynthia Magalhães Pinto Godoi (2013)
In the context of the (current) administration, the State must assume an ever more legitimate, transparent, efficient and accountable, with the adoption of institutionalized controls constantly improved, serving at the same time as limiting the activities of agents and as a thermometer of democracy in a given society, be true shield corruption and misconduct, with a constitutional duty to be accountable as a major obligations that are imposed on the public officer. Noteworthy are the Courts of Auditors (TC) with the constitutional authority of administrative and financial oversight of government actions (MORAES, 2008), competing them, including monitoring the application of any funds transferred by the corresponding entities by agreement and apply those responsible in case of illegality or irregularity expense accounts, the penalties provided by law. Moreover, the federal aspect, proposed by the 1988 Constitution, has structured a system of division of powers, through a series of activities shifted to the local level, in order to provide more efficient public spending and give rise to more responsiveness and accountability (NÓBREGA, 2011), extending the capability of spending by municipalities (PRADO, 2003 a) and intergovernmental transfers of funds as an important arrangement for their equitable distribution, based on constitutional provisions, statutory or voluntary. Whereas the Constitution refers to the control of voluntary transfers, the Court of Accounts of the Union and the States, who have the competence to supervise the municipalities, under Articles 75 and 31, both of the Magna Carta, assume this role using control mechanisms, among which, a little known, is taking special accounts (tce), with the goal of protecting the public treasury and the agents responsible embezzlers of public funds. Under the aspect of control and accountability for acts of public officials against his duty to account for funds transferred by voluntary transfers (covenants), it is intended to study tce, structured in six chapters, check whether it is an instrument of control effective accountability of public agents causing damage to the treasury, within Minas Gerais, as irregularities in accountability agreements signed with municipalities, and their consequences in administrative, civil, criminal and electoral. Through literature, documentary and exploratory, it was possible to delay the adoption of the instrument by tce Executive Mining and processing delays at the Court of Auditors (TCEMG), weakening accountability objectified by the instrument, which points to little or no effectiveness as the accountability of public officials with the duty of responsibility in covenants. Nevertheless, the work highlights the importance of the instrument and the need to make it faster as exceptional mechanism of control.